Implementasi Manajemen Berbasis Sekolah Dalam Upaya Meningkatkan Mutu Lulusan Di Sekolah Menengah Atas - Gumelar, Wahyu Satya (Media Nusantara, 2022)
School-Based Management is a model of school management by giving greater authority at the school level to directly manage their own schools so that schools have the responsibility in determining school programs. School-Based Management is a form of decentralization reform that promotes democratic participation. The implementation of education decentralization or called Educational autonomy has not yet fully worked out as expected, due to the unpreparedness of social, political and economic institutions. Educational autonomy will have an effect on the curriculum, administrative efficiency, income and education costs as well as its distribution. This study aims to find out the planning, implementation, evaluation and results achieved in implementing school-based management in improving graduates. which underlies this research is the theory of school-based management, integrated quality management, school committees, and graduate quality. This research uses a descriptive qualitative approach with interview, observation, and documentation study techniques. The research results can be concluded that; (1) School-based management planning in improving the quality of graduates begins with preparing the vision, mission, objectives, quality targets, and strategic plans of each institution with reference to the National Education Standards by involving all stakeholders; (2) The implementation of school-based management has referred to the Strategic Plan and the responsibility has been delegated to the Quality Management Team; (3) School-based management evaluation is carried out with an internal audit system and an external audit system; (4) The result achieved is customer satisfaction. However, there are still some aspects of the service that are not satisfactory, including aspects of infrastructure, and the environment.